Answer :

Answer:

A.  12x² + 15xy + 18x

B.  - 12x² + 18xy + 24x

C.  10x² - 31x - 14

D.   x² - 36

3a.  x = 8

3b.  x = 3

Step-by-step explanation:

A.  3x ( 4x + 5y +6 )                        C.  ( 2x - 7 ) ( 5x + 2 )

    12x² + 15xy + 18x                             10x² + 4x - 35x - 14

                                                             10x² - 31x - 14

B.  6x ( 3y - 2x + 4 )

    18xy - 12x² + 24x                         D. ( x + 6 ) ( x - 6 )

     -12x² + 18xy + 24x                           x² - 6x + 6x - 36

                                                              x² - 36

3a.  5/4x + 2 = 12                             3b.  7/3x - 2 = 5/3x

      5/4x = 12 - 2                                     -2 = 5/3x - 7/3x

      5/4x = 10                                          -2 = - 2/3x

      x = 10 · 4/5                                       -2/3x = -2

      x = 8                                                  x = 3                                        

     

Other Questions